RT-qPCR-Based Assessment of the Efficacy of 222 nm UVC Irradiation in Reducing SARS-CoV-2 Surface Contamination - Jurate Gruode; Arvydas Martinkenas; Mindaugas Kurmis; Darius Drungilas; Zydrunas Lukosius; Arturas Tadzijevas; Rimantas Didziokas; Valdas Jankunas; Deivydas Sapalas (Sensors, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), has emerged as a serious threat to human health worldwide. The effective disinfection of surfaces contaminated with SARS-CoV-2 may help prevent its spread. The aim of this study is to determine the duration required for viral RNA elimination by 222 nm far ultraviolet light using RT-qPCR as a tool. This study investigated the effect of 222 nm UVC irradiation on SARS-CoV-2 RNA in an in vitro experiment. The results showed that the copy number of SARS-CoV-2 RNA did not change even after 300 s of 222 nm UVC irradiation at 0.1 mW/cm2, but extending the exposure to more than 600 s reduced the number of copies of SARS-CoV-2 virus significantly. However, to fully validate the results and enhance the robustness of the findings, it is crucial to increase the number of samples analyzed in future experiments.